THE ROLE OF DIDACTIC CONDITIONS IN THE USE OF DIGITAL TECHNOLOGIES BY TEACHERS OF TECHNOLOGICAL EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today, Information and communication technology has become a way of life in which children are drawn. Today's children are beginning to use digital tools at a very young age, so that the school should respond to the needs of students. Also today it is impossible for any profession performs without the help of information technology. The computer and the Internet gives us endless possibilities and resources in improving the quality of work. Even in education, computer skills and additional equipment are needed, because they create great opportunities for teachers and inspire curiosity, imagination and interest of students. Teachers should not oppose change, but they should use new technology for better quality teaching and make it more interesting. The use of technology will positively improve results faculty and students. Teachers must carefully plan the use and integration of technology in teaching. How to integrate technology into teaching mainly depends on how many computers has at its disposal.